Inhibition of CMP-sialic acid transport by endogenous 5-methyl CMP. - Shivani Ahuja (Public Library of Science (PLoS), 2021)
Nucleotide-sugar transporters (NSTs) transport nucleotide-sugar conjugates into the Golgi lumen where they are then used in the synthesis of glycans. We previously reported crystal structures of a mammalian NST, the CMP-sialic acid transporter (CST) (Ahuja and Whorton 2019). These structures elucidated many aspects of substrate recognition, selectivity, and transport; however, one fundamental unaddressed question is how the transport activity of NSTs might be physiologically regulated as a means to produce the vast diversity of observed glycan structures. Here, we describe the discovery that an endogenous methylated form of cytidine monophosphate (m5CMP) binds and inhibits CST. The presence of m5CMP in cells results from the degradation of RNA that has had its cytosine bases post-transcriptionally methylated through epigenetic processes. Therefore, this work not only demonstrates that m5CMP represents a novel physiological regulator of CST, but it also establishes a link between epigenetic control of gene expression and regulation of glycosylation.